Mechanical Testing of the New Cage for Tibial Tuberosity Advancement with the Cranial Implant Fixation (TTA CF) Technique—Ex Vivo Study on Sheep Model - Yauheni Zhalniarovich; Paulina Przyborowska-Zhalniarovich; Angelika Tobolska; Marta Mieszkowska; Justyna Abako; Magdalena Morawska-Kozłowska; Marcin Mieszkowski; Dariusz Onichimowski (Animals, 2022)
Background: Modifications of tibial tuberosity advancement are well accepted for cranial cruciate rupture repair. We compared the loads that were needed to pull the TTA CF cage out in the two groups. The first group consisted of five sheep in which osteotomy and TTA CF cage fixation were performed as assumed preoperatively. The second group consisted of five sheep in which intraoperative or postoperative discrepancies from preoperative planning were found. This is also the first report describing biomechanical testing after tibial tuberosity advancement with cranial implant fixation (TTA CF) surgical procedures. Results: A total of 10 ovine proximal tibiae were tested biomechanically by tearing out TTA CF implants from the bone. The mean maximal loaded forces to pull out the cage in Group 1, in which fixation of the implant was performed as assumed preoperatively, was 878 ± 61 N, and in Group 2, in which discrepancies from preoperative planning were found, was 330 ± 55 N. The mean implant displacement under maximal load to failure was 2.6 mm and 2.2 mm in Groups 1 and 2, respectively. There was a significant difference between Group 1 and Group 2 in the maximal loads-to-failure; however, the difference in the displacement at maximal loaded forces to pull out the cage was not significant between the groups. Conclusions: The mean maximal loaded forces to pull out the cage was significantly lower in Group 2, where discrepancies from preoperative planning were found (878 ± 61 N vs. 330 ± 55 N). The lower forces that were needed to extract the TTA CF implant from the tibia can lead to the conclusion that biointegration of the implant is also weaker. Correct positioning of the osteotomy line and TTA CF implant is essential for good biointegrity and thus for limiting complications in the form of tibial tuberosity avulsion fracture or tibial shaft fracture.